Method for producing needle coke by using FCC (fluid catalytic cracking) slurry oil

By using a hydrogenation catalyst with a multi-stage pore structure to treat FCC oil slurry, the problems of low true density and large thermal expansion coefficient of needle-shaped coke in the prior art are solved, efficient impurity removal and crystal structure optimization are achieved, and needle-shaped coke is improved. The quality meets the performance requirements of high-power electrodes.

CN119161887AInactive Publication Date: 2024-12-20LUOYANG HONGLIAN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411657589.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the true density of needle-shaped coke is low and the thermal expansion coefficient is large, making it difficult for domestic coke to completely replace imported coke. The main reason is that the conditions for raw material pretreatment and carbonization coke formation process need to be improved, and the existing catalyst channel structure cannot process large molecules at the same time. and small molecule impurities lead to poor impurities removal effect and affect the full development of the crystal structure.

Method used

Using homemade hydrogenation catalysts, including composite support and active elements, improve the activity and selectivity of the catalyst through hydrotreatment of multi-stage pore structures, combine with FCC oil slurry for hydrotreatment, and then staged carbonization and calcination to optimize the raw material structure. To improve the quality of needle coke.

Benefits of technology

It significantly improves the activity and desulfurization effect of the hydrogenation catalyst, improves the true density and conductivity of the needle coke, reduces the thermal expansion coefficient, and meets the quality requirements of the needle coke for high-power electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161887A_ABST
    Figure CN119161887A_ABST
Patent Text Reader

Abstract

The invention provides a method for producing needle coke by using FCC slurry oil, and belongs to the technical field of needle coke, the production method comprises the steps of filtration separation, reduced pressure distillation, solvent extraction, hydrotreatment, carbonization coke formation and calcination; in hydrotreatment, a hydrogenation catalyst comprises a composite carrier and 10-45% by mass of active elements, and the active elements comprise Ni and Mo in a molar ratio of 1: (3-6), and at least one of Co, V or W; the composite carrier comprises the following components in percentage by mass: 50-80% of aluminum oxide and 20-50% of silicon oxide; the specific surface area of the composite carrier is 200-400m < 2 > / g, the composite carrier is of a hierarchical pore structure with micropores, mesopores and macropores, and the ratio of the pore volume of the micropores to the total pore volume is lt; the pore volume of mesopores accounts for 50-65% of the total pore volume, and the pore volume of macropores accounts for 30-50% of the total pore volume. The self-made hydrogenation catalyst is used for hydrotreating the raw materials, so that the activity of the catalyst and the selectivity of hydrodesulfurization can be effectively improved, and the desulfurization rate of the materials is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of needle coke, in particular to a method for producing needle coke by utilizing FCC oil slurry. Background Art

[0002] Needle coke is a high-quality carbon material that has been vigorously developed in the 1970s. It is a silver-gray solid with a metallic luster. Its surface has obvious slender needle-like or fibrous textures. Under a microscope, it has a distinct anisotropic fibrous structure, so it is called needle coke. Because of its low content of elements such as sulfur and nitrogen, low thermal expansion coefficient and suitable resistivity, it is the most important raw material for preparing high power (HP) and ultra-high power (UHP) electrodes. The high power and ultra-high power graphite electrodes made from it have outstanding advantages such as low resistivity, small thermal expansion coefficient, strong heat shock resistance, high mechanical strength and good oxidation resistance. Compared with ordinary electrode steelmaking, the smelting time of electric furnace steelmaking can be shortened by 30~50%, and the power consumption can be reduced by 20~50%; when needle coke is heated to above 2000℃, the hexagonal carbon atom plane network structure of its microstructure is perfectly developed and transformed into a regular and ordered three-dimensional layered graphite crystal structure. Therefore, it has a high degree of graphitization and excellent conductivity, a large lithium storage capacity, and a higher theoretical capacity and excellent low-temperature performance than graphite materials. It has gradually become a high-quality raw material for negative electrode materials of lithium-ion batteries. With the development of society, HP and UHP electrodes with better performance have become the market demand. In order to prepare HP and UHP with better performance, the needle coke used for electrodes is generally required to have high true density, low coefficient of thermal expansion (CTE), high strength, low resistivity and good oxidation resistance. In recent years, my country's needle coke industry has developed rapidly, but high-quality needle coke (true density ≥ 2.13g / cm 3 , thermal expansion coefficient CET≤1.0×10 -6 / ℃) still mainly relies on imports.

[0003] The production process of needle coke mainly includes three parts: raw material pretreatment, carbonization and coking, and calcination. Among them, the raw material pretreatment methods include hydrogenation treatment, two-stage thermal polycondensation, solvent treatment, etc. In order to prepare high-quality needle coke, the current preparation process has the following shortcomings: First, the current domestic oil-based needle coke raw materials mainly include heavy distillate oils such as thermal cracking residue, catalytic cracking slurry (FCC slurry), vacuum residue, etc., and their sulfur content mostly exceeds 0.5%, which requires the use of catalysts for desulfurization. Since the needle coke raw materials not only include aromatics and long-chain macromolecules, the smaller pores will prevent these components from entering the pores of the catalyst for reaction, but also include impurities such as sulfur and nitrogen of different sizes. If the pores are too large, the removal effect of impurities cannot be guaranteed. Therefore, the pore structure of the carrier in the catalyst has an important influence on the hydrogenation treatment effect. However, the pores of the catalyst in the prior art are generally mesoporous pores with uniform pore sizes, and it is impossible to simultaneously hydrogenate the macromolecules and small molecules in the raw materials, and thus it is impossible to meet the requirements for producing high-quality needle coke raw materials. Second, the raw materials (such as FCC oil slurry) undergo pyrolysis and polycondensation during the carbonization process to form mesophase globules, which grow, fuse, and collide to form a wide-area mesophase. The content and properties of the mesophase, as well as the degree of matching with the "airflow coke pulling" effect in the subsequent solidification process, are the key to determining the quality of needle coke. Existing technologies do not adequately control the liquid phase carbonization process and the airflow coke pulling process, and cannot fully develop high-quality crystal structures, resulting in low anisotropic fiber structure content and the inability to stably produce needle coke for ultra-high power electrodes.

[0004] The main problems with needle coke for electrodes currently produced in my country are low true density and large coefficient of thermal expansion (CTE). Therefore, domestic coke cannot completely replace imported coke. The main reason is that in the production process, the pretreatment of raw materials and the carbonization and coking process conditions need to be further improved. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a method for producing needle coke using FCC slurry oil, wherein the raw material is hydrogenated using a homemade hydrogenation catalyst, which can effectively improve the activity of the hydrogenation catalyst and the selectivity of hydrodesulfurization. When the catalyst is working, the desulfurization effect of the material is significantly improved.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for producing needle coke using FCC slurry oil, mainly comprising filtering and separation, vacuum distillation, solvent extraction, hydrogenation treatment, carbonization and coking, and calcination steps; in the hydrogenation treatment, hydrogenation treatment is performed in combination with a sulfurized hydrogenation catalyst; the hydrogenation catalyst comprises a composite carrier and an active element, the mass percentage of the active element in the hydrogenation catalyst is 10-45%, the active element comprises a main active element and a secondary active element, the main active element comprises Ni and Mo in a molar ratio of 1:(3-6), and the secondary active element is at least one of Co, V or W; The composite carrier contains 50-80% alumina and 20-50% silica by mass; the specific surface area of ​​the composite carrier is 200-400m 2 / g, a multi-level pore structure with micropores, mesopores and macropores, the size of the micropores is less than 2nm, the size of the mesopores is 2nm-50nm, and the size of the macropores is greater than 50nm; the ratio of the pore volume of the micropores to the total pore volume is <5%, the ratio of the pore volume of the mesopores to the total pore volume is 50-65%, and the ratio of the pore volume of the macropores to the total pore volume is 30-50%.

[0007] Furthermore, the preparation method of the hydrogenation catalyst is: Step 1: polyvinyl alcohol, alumina sol, silica sol and urea solution are mixed to form a carrier precursor, and then liquid nitrogen is poured for rapid cooling, followed by freeze drying to obtain an intermediate; the intermediate is calcined at 400-600° C. for 10-20 hours to obtain a composite carrier comprising alumina and silica; Step 2: dissolving ammonium molybdate and nickel nitrate in deionized water, and adjusting the pH to 7.1-8.0 with ethylenediamine to obtain solution A; dissolving a metal salt containing a secondary active element in deionized water, and stirring to dissolve to obtain solution B; Step 3: Place the composite carrier in solution A, immerse it in vacuum for 0.5 to 2 hours, and then place it in an oven and dry it at 100° C. for 10 minutes; Step 4: Place the composite carrier in solution B again, and immerse it under vacuum for 0.5 to 2 hours. Place the impregnated composite carrier in a reaction kettle and seal it. Place the reaction kettle in an oven, hydroheat it at 150 to 170° C. for 12 to 48 hours, and cool it. Step 5: After the reactor cools to room temperature, the composite carrier is taken out, and after multiple ultrasonic washings, it is placed in an oven and dried at 60-100°C for 12-24 hours to obtain a catalyst precursor; Step 6: calcining the catalyst precursor at 400-600° C.; Step 7: reducing the calcined product to obtain a hydrogenation catalyst.

[0008] Furthermore, in step 1, the mass percentages of urea in polyvinyl alcohol, alumina sol, silica sol and urea solution are (1-2):(5-8):(2-5):(0.35-1).

[0009] Furthermore, in step 1, the freeze-drying temperature is ≤-40°C, the vacuum pressure is ≤15Pa, and the time is 20~40h.

[0010] Furthermore, in step 2, the metal salt containing the secondary active element includes at least one of cobalt nitrate, ammonium metavanadate or ammonium metatungstate.

[0011] Furthermore, in step seven, the reduction conditions are: the reducing gas flow rate is 15-20 mL / min, the reduction time is 2-4 h; the reduction temperature is 550-600° C., and the heating rate is 2-8° C. / min.

[0012] Further, the FCC oil slurry is used as a raw material, and is filtered and separated to obtain FCC filtered oil; the FCC filtered oil is cut by vacuum distillation to obtain aromatic narrow fraction oil at a distillation temperature of 390-440°C; the aromatic narrow fraction oil is subjected to solvent extraction to enrich aromatics to obtain extracted oil; the extracted oil is used as a raw material, and is hydrogenated in combination with a sulfurized hydrogenation catalyst to remove coke-prone components to obtain hydrogenated oil; the hydrogenated oil is carbonized and coked in stages to obtain green coke; and finally the green coke is calcined to obtain needle coke.

[0013] Furthermore, the hydrogenated oil is subjected to a carbonization and coking treatment in stages, as follows: The first stage: the reaction pressure is 1-2 MPa, the temperature is increased to 380°C at a heating rate of 10-12°C / min and kept at this temperature for 1-2 hours; The second stage: the reaction pressure is 2-2.5 MPa, the temperature is increased to 440°C at a heating rate of 6-8°C / min and kept at this temperature for 2-10 hours; The third stage: the temperature is maintained at 440℃, the reaction pressure is increased to 15~20MPa, and the pressurization time is 0.5h; The fourth stage: the reaction pressure is 0.5-1 MPa, the temperature is increased to 500°C at a heating rate of 2-3°C / min and kept at this temperature for 1-5 hours; The fifth stage: cooling to room temperature to obtain green coke.

[0014] Furthermore, the green coke is crushed and screened, and the screened material is placed in a high-temperature furnace, and nitrogen is introduced at a gas rate of 70 mL / min. After maintaining for 20 minutes, under the protection of nitrogen, the temperature is increased from room temperature to 800°C at a heating rate of 7°C / min and kept warm for 2 hours, and then increased to 1400°C at a heating rate of 2°C / min, and kept at 1400°C for 120 minutes, and then the heating is stopped. While continuously introducing nitrogen, the temperature is cooled until it drops below 400°C, and the introduction of nitrogen is stopped. The temperature is naturally cooled to room temperature to obtain needle coke.

[0015] Furthermore, the reaction temperature of the hydrotreatment is 360-400° C., the reaction pressure is 4-10 MPa, and the reaction time is 60-150 min.

[0016] Beneficial effects: 1) The present invention adopts an impregnation method to prepare a hydrogenation catalyst, and loads Ni, Mo, and at least one active element of Co, V or W on a composite carrier, which has the following advantages: (1) The activity of the hydrogenation catalyst and the selectivity of hydrodesulfurization can be effectively improved. When the catalyst is working, the desulfurization rate of the material is significantly improved. (2) The composite carrier serves as the skeleton of the hydrogenation catalyst, carries the active elements, and provides stable support for it. In terms of mass fraction, the composite carrier contains 50-80% of aluminum oxide and 20-50% of silicon oxide, combining the advantages of aluminum oxide and silicon oxide to form a multi-level pore structure, further improving the specific surface area and porosity. This is not only conducive to the rapid diffusion of reactant molecules, but also can effectively accommodate more active elements, thereby improving the catalytic activity and physicochemical stability of the hydrogenation catalyst. By adjusting the ratio of aluminum oxide and silicon oxide and the preparation process, the pore structure of the composite carrier can be precisely controlled, thereby optimizing the dispersibility of the active elements on the composite carrier. This helps to improve the catalytic activity and selectivity of the hydrogenation catalyst. (3) In the hydrogenation catalyst, the mass percentage of active elements is 10~45%. This ratio has been carefully adjusted to achieve the best catalytic effect. The active elements include main active elements and secondary active elements. The main active elements are composed of Ni and Mo, and their molar ratio is precisely controlled in the range of 1: (3~6). The synergistic effect of Ni and Mo performs well in hydrodesulfurization and hydrodenitrogenation, and can significantly improve the activity and selectivity of the hydrogenation reaction, so that the hydrogenation catalyst exhibits excellent performance in the hydrogenation process. The addition of secondary active elements further enhances the activity and stability of the catalyst. The interaction between the secondary active elements and the main active elements makes the hydrogenation catalyst more flexible and efficient in dealing with complex reaction systems. (4) The hydrogenation catalyst has a multi-level pore structure, including micropores, mesopores and macropores. This structure enables the catalyst to have higher mass transfer efficiency and larger reaction area during the hydrogenation process. Micropores are conducive to the adsorption of small molecules, while mesopores and macropores are conducive to the diffusion and reaction of large molecules. By precisely controlling the pore volume distribution of micropores, mesopores and macropores, the desulfurization rate is guaranteed, thereby improving the quality of the product.

[0017] 2) In the preparation of the hydrogenation catalyst, polyvinyl alcohol, alumina sol, silica sol and urea solution are first mixed to form a carrier precursor. Then, the carrier precursor is quickly poured into liquid nitrogen, and the ultra-low temperature of liquid nitrogen is used to achieve rapid cooling to fix its structure. After freezing, the sample is placed in a freeze dryer, and after a long period of vacuum drying, the moisture is removed to obtain an intermediate with a stable structure and good pore distribution. Subsequently, the intermediate is placed in a high-temperature furnace and calcined in a temperature range of 400 to 600°C for 10 to 20 hours to enhance its thermal stability and mechanical strength, and finally a composite carrier is obtained. After that, the composite carrier is used for step-by-step impregnation operations to obtain the final hydrogenation catalyst. Among them, the removal of polyvinyl alcohol and the growth of alumina produce micropores and mesopores, and the removal of ice crystals in the polyvinyl alcohol-assisted sol-gel-freeze drying process forms a unique macroporous network, so that the composite carrier provides more active sites and has a higher specific surface area.

[0018] 3) The present invention adopts a staged treatment during the carbonization and coking step to improve the quality of the final needle coke. In the first stage, the reaction pressure is set to 1-2 MPa to ensure that the raw materials can be stably preliminarily pyrolyzed and carbonized during the heating process. The heating rate is controlled within the range of 10-12°C / min, which is a relatively fast heating rate, aiming to quickly reach a suitable reaction temperature while avoiding excessive pyrolysis or unnecessary side reactions caused by the raw materials staying at low temperatures for a long time. As the temperature gradually increases, the light components in the raw materials begin to volatilize, while the heavy components begin to undergo pyrolysis and polycondensation reactions to form a preliminary carbonized structure. When the temperature reaches 380°C, the first stage ends. Entering the second stage, the reaction pressure increases slightly and is set to 2-2.5MPa, ensuring a high yield of carbonized products. At the same time, the heating rate slows down to 6-8℃ / min to give the raw materials more time to undergo pyrolysis and polycondensation reactions to form mesophase spheres. In this stage, the temperature reaches 440℃, and the mesophase spheres are initially generated, while the microcrystals are initially arranged and oriented. In the third stage, the temperature is maintained at 440℃, while the reaction pressure is increased to 15-20MPa. The present invention disturbs the newly generated mesophase spheres through a short and obvious pressurization treatment, so that some of the mesophase spheres continue to collide, grow, and merge, increasing the content of the wide-area streamlined structure, thereby improving the quality of the final needle coke. After entering the fourth stage, the reaction pressure is reduced to 0.5-1MPa to reduce the thermal stress inside the coke at high temperature and avoid the destruction of the coke structure. At the same time, the heating rate is further slowed down to 2-3℃ / min to give the raw materials more time to undergo high-temperature carbonization reactions and make the coke structure more stable. At a temperature of 500°C, the remaining light components in the raw materials continue to volatilize, while the density and hardness of the raw coke gradually increase. Finally, the raw coke product is obtained by entering the cooling stage.

[0019] 4) The present invention places the crushed and screened coke particles in a high-temperature furnace. In the high-temperature furnace, nitrogen is first introduced. Nitrogen can effectively protect the coke from being oxidized at high temperatures, and at the same time remove the air in the furnace to create an oxygen-free environment for subsequent reactions. The nitrogen gas velocity is stably controlled at 70 mL / min, which can not only ensure the oxygen-free environment in the furnace, but also avoid heat loss caused by excessive nitrogen flow. This gas velocity is maintained for about 20 minutes to fully preheat the coke particles in the nitrogen atmosphere and prepare for the subsequent high-temperature graphitization process. Under the protection of nitrogen, the temperature was raised from room temperature to 800°C at a heating rate of 7°C / min, which could protect the fiber structure of needle coke, reduce large-diameter pores on the coke surface, and increase the true density of needle coke. The crystal structure of needle coke was improved, and it had excellent true density. After reaching 1400°C, the temperature was kept constant for 120 minutes, which could further increase its true density and reduce its thermal expansion coefficient. Finally, natural cooling to room temperature was adopted to improve the particle strength of needle coke. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the microstructure diagram of the needle coke prepared in Example B-1. DETAILED DESCRIPTION

[0021] In the field of chemistry and materials science, needle coke, as a high-performance carbon material, is widely used in electrode materials, high-performance graphite products, and advanced composite materials due to its unique physical and chemical properties. However, the traditional production method often has problems such as low true density and high thermal expansion coefficient of the prepared needle coke. To solve these problems, this study proposes a method for producing needle coke using FCC (catalytic cracking) oil slurry, which mainly includes the following steps: using FCC oil slurry as raw material, filtering and separating to obtain FCC filtered oil; cutting the FCC filtered oil by vacuum distillation to obtain aromatic narrow fraction oil at a distillation temperature of 390-440°C; solvent extraction treatment of the aromatic narrow fraction oil to enrich aromatics to obtain extracted oil; using the extracted oil as raw material, hydrogenation treatment combined with a hydrogenation catalyst to remove the coke-prone components to obtain hydrogenated oil; carbonizing the hydrogenated oil in stages to obtain green coke; and finally calcining the green coke to obtain needle coke. Each step is aimed at removing impurities, optimizing the raw material structure, and ultimately obtaining high-quality needle coke products. In particular, a high-performance hydrogenation catalyst is introduced into the hydrogenation process, which achieves efficient conversion of FCC slurry oil and significant improvement in the quality of needle coke. The innovative steps of the present invention are described in detail below.

[0022] <Hydrogenation treatment> The present invention combines a hydrogenation catalyst for hydrogenation treatment during hydrogenation treatment. The hydrogenation catalyst of the present invention comprises a composite carrier and an active element, wherein the composite carrier comprises 50-80% of aluminum oxide and 20-50% of silicon oxide by mass fraction, the active element comprises a main active element and a secondary active element, the main active element comprises Ni and Mo in a molar ratio of 1:(3-6), and the secondary active element is at least one of Co, V or W.

[0023] Compared with the single carrier commonly used in the prior art, such as a single alumina carrier, the present invention uses a composite carrier, and by adjusting the ratio of alumina and silicon oxide, the pore structure of the carrier can be precisely controlled, thereby optimizing the dispersion of active elements on the carrier. This helps to improve the catalytic activity and selectivity of the catalyst.

[0024] In addition, the specific surface area of ​​the composite carrier is between 200 and 400 m² / g. Its pore distribution presents a multi-level pore structure, which includes three different types of pores: micropores, mesopores and macropores. The micropore size is less than 2nm, which mainly acts as a molecular sieve, selectively allowing molecules of a certain size to pass through; the mesopore size is 2nm to 50nm, which is the main channel for the diffusion of reactant molecules and product molecules; the macropore size is greater than 50nm, which is mainly used to accommodate active elements and provide sufficient space to relieve stress during the catalytic process.

[0025] In terms of pore volume distribution, the ratio of micropore volume to total pore volume is less than 5%. This design not only ensures the selective screening function of micropores, but also avoids diffusion restriction caused by too many micropores. The ratio of mesopore volume to total pore volume is as high as 50-65%, and the ratio of macropore volume to total pore volume is 30-50%. The optimization of this ratio makes mesopores and macropores the main channels for the diffusion of reactant molecules and product molecules, thereby greatly improving the rate of hydrogenation reaction. At the same time, it provides sufficient attachment space for active elements, helps to relieve stress in the catalytic process, and improves the stability and service life of the catalyst.

[0026] Because the catalyst has a multi-level pore structure, the reactant molecules can smoothly enter the catalyst to react. Micropores are conducive to the adsorption and reaction of small molecular impurities, while mesopores and macropores are conducive to the diffusion and reaction of large molecular hydrocarbons. This structure makes the hydrogenation reaction more efficient and thorough.

[0027] The preparation method of the above hydrogenation catalyst is: Step 1: polyvinyl alcohol, alumina sol, silica sol and urea solution are mixed to form a carrier precursor, and then liquid nitrogen is poured for rapid cooling, followed by freeze drying, the freeze drying temperature is ≤-40°C, the vacuum pressure is ≤15Pa, and the time is 20-40h to obtain an intermediate; the intermediate is calcined at 400-600°C for 10-20h to obtain a composite carrier of alumina and silica; Step 2: dissolving ammonium molybdate and nickel nitrate in deionized water, and adjusting the pH to 7.1-8.0 with ethylenediamine to obtain solution A; dissolving a metal salt containing a secondary active element in deionized water, and stirring to dissolve to obtain solution B, wherein the metal salt containing a secondary active element includes at least one of cobalt nitrate, ammonium metavanadate or ammonium metatungstate; Step 3: Place the composite carrier in solution A, immerse it in vacuum for 0.5 to 2 hours, and then place it in an oven and dry it at 100° C. for 10 minutes; Step 4: Place the composite carrier in solution B again, and immerse it under vacuum for 0.5 to 2 hours. Place the impregnated composite carrier in a reaction kettle and seal it. Place the reaction kettle in an oven, hydroheat it at 150 to 170° C. for 12 to 48 hours, and cool it. Step 5: After the reactor cools to room temperature, the composite carrier is taken out, and after multiple ultrasonic washings, it is placed in an oven and dried at 60-100°C for 12-24 hours to obtain a catalyst precursor; Step 6: calcining the catalyst precursor at 400-600° C.; Step seven, reducing the calcined product, the flow rate of reducing gas (hydrogen, or a mixture of hydrogen and argon in a volume ratio of 2:1) is 15-20 mL / min, the reduction time is 2-4 h; the reduction temperature is 550-600° C., and the heating rate is 2-8° C. / min, to obtain a hydrogenation catalyst.

[0028] It should be noted that the mass percentages of urea in polyvinyl alcohol, alumina sol, silica sol and urea solution are (1-2):(5-8):(2-5):(0.35-1).

[0029] During the hydrogenation process, impurity molecules (such as sulfur compounds, nitrogen compounds, etc.) in FCC slurry are first adsorbed by active sites on the surface of the hydrogenation catalyst. Under the action of the catalyst, these impurity molecules are activated and react with hydrogen to generate small molecules such as hydrogen sulfide and ammonia that are easy to remove. The FCC slurry that has been hydrogenated enters the carbonization and coking stage, where a series of complex chemical reactions occur at high temperatures, including pyrolysis, polycondensation, dehydrogenation, and aromatization. These reactions cause the carbon atoms in the raw materials to rearrange and recombine, ultimately forming needle coke with special textures and structures. Due to the removal of impurities and optimization of raw materials during the hydrogenation process, the product quality of the needle coke that is finally formed is significantly improved.

[0030] <Carbonization into coke> The hydrogenated oil is carbonized and coked in stages, as follows: The first stage: the reaction pressure is 1-2 MPa, the temperature is increased to 380°C at a heating rate of 10-12°C / min and kept at this temperature for 1-2 hours; The second stage: the reaction pressure is 2-2.5 MPa, the temperature is increased to 440°C at a heating rate of 6-8°C / min and kept at this temperature for 2-10 hours; The third stage: the temperature is maintained at 440℃, the reaction pressure is increased to 15~20MPa, and the pressurization time is 0.5h; The fourth stage: the reaction pressure is 0.5-1 MPa, the temperature is increased to 500°C at a heating rate of 2-3°C / min and kept at this temperature for 1-5 hours; The fifth stage: cooling to room temperature to obtain green coke.

[0031] <Calcination> The raw coke is crushed and screened, and the screened material is placed in a high-temperature furnace, and nitrogen is introduced at a stable gas rate of 70 mL / min. After maintaining for about 20 minutes, the temperature is increased from room temperature to 800°C at a heating rate of 7°C / min under the protection of nitrogen, and kept warm for 2 hours. Then, the temperature is increased to 1400°C at a heating rate of 2°C / min, and the temperature is kept constant at 1400°C for 120 minutes. After that, the heating is stopped, and the temperature is cooled while continuously introducing nitrogen until it drops below 400°C, and the introduction of nitrogen is stopped. The temperature is naturally cooled to room temperature to obtain needle coke.

[0032] It should be noted that other contents mentioned in the present invention belong to the prior art and will not be described in detail here. The technical solution of the present invention is described in detail below in combination with specific embodiments and comparative examples.

[0033] Example A-1 The preparation method of the hydrogenation catalyst is: Step 1, weighing polyvinyl alcohol, alumina sol, silica sol and urea according to the mass percentage of 1:5:2:0.35, preparing urea into a urea solution with a concentration of 10 mol / L, mixing polyvinyl alcohol, alumina sol, silica sol and urea solution to obtain a carrier precursor; pouring liquid nitrogen into the carrier precursor for rapid cooling, and then freeze-drying it at a freeze-drying temperature of -40°C, a vacuum pressure of 15 Pa, and a time of 40 hours to obtain an intermediate; calcining the intermediate at 400°C for 20 hours to obtain a composite carrier; Step 2: Dissolve ammonium molybdate and nickel nitrate in deionized water, and adjust the pH to 7.1 with ethylenediamine to obtain solution A; dissolve cobalt nitrate, ammonium metavanadate and ammonium metatungstate in deionized water, and stir to dissolve to obtain solution B; Step 3: Place the composite carrier in solution A, immerse it in vacuum for 0.5 h, and then place it in an oven and dry it at 100° C. for 10 min; Step 4: Place the composite carrier in solution B again, and immerse it under vacuum for 0.5 h. Place the impregnated composite carrier in a reaction kettle and seal it. Place the reaction kettle in an oven, hydroheat it at 150° C. for 48 h, and cool it. Step 5: After the reactor cools to room temperature, the composite carrier is taken out, ultrasonically washed several times, and then placed in an oven and dried at 100° C. for 12 hours to obtain a catalyst precursor; Step 6, calcining the catalyst precursor at 600° C.; Step 7: Reduce the calcined product, the reducing gas (hydrogen) flow rate is 15 mL / min, the reduction time is 2 h; the reduction temperature is 550° C., and the heating rate is 2° C. / min, to obtain a hydrogenation catalyst.

[0034] Example A-2 Step 1, weighing polyvinyl alcohol, alumina sol, silica sol and urea according to the mass percentage of 2:8:5:1, preparing urea into a urea solution with a concentration of 10 mol / L, mixing polyvinyl alcohol, alumina sol, silica sol and urea solution to obtain a carrier precursor; pouring liquid nitrogen into the carrier precursor for rapid cooling, and then freeze-drying it at a freeze-drying temperature of -50°C, a vacuum pressure of 20 Pa, and a time of 20 hours to obtain an intermediate; calcining the intermediate at 600°C for 10 hours to obtain a composite carrier; Step 2: Dissolve ammonium molybdate and nickel nitrate in deionized water, and adjust the pH to 8 with ethylenediamine to obtain solution A; dissolve cobalt nitrate and ammonium metatungstate in deionized water, and stir to dissolve to obtain solution B; Step 3: Place the composite carrier in solution A, immerse it under vacuum for 2 hours, and then put it in an oven and dry it at 100°C for 10 minutes; Step 4: Place the composite carrier in solution B again, and immerse it under vacuum for 2 hours. Place the impregnated composite carrier in a reaction kettle and seal it. Place the reaction kettle in an oven, hydroheat it at 170° C. for 12 hours, and cool it. Step 5: After the reactor cools to room temperature, the composite carrier is taken out, ultrasonically washed several times, and then placed in an oven and dried at 60° C. for 24 hours to obtain a catalyst precursor; Step 6, calcining the catalyst precursor at 400° C.; Step 7: Reduce the calcined product, the reducing gas (a mixture of hydrogen and argon in a volume ratio of 2:1) flow rate is 20 mL / min, the reduction time is 4 h; the reduction temperature is 600 ° C, and the heating rate is 8 ° C / min, and the hydrogenation catalyst is obtained.

[0035] Example A-3 The preparation method of the hydrogenation catalyst is: Step 1, weighing polyvinyl alcohol, alumina sol, silica sol and urea according to the mass percentage of 1:6:3:0.5, preparing urea into a urea solution with a concentration of 10 mol / L, mixing polyvinyl alcohol, alumina sol, silica sol and urea solution to obtain a carrier precursor; pouring liquid nitrogen into the carrier precursor for rapid cooling, and then freeze-drying it at a freeze-drying temperature of -50°C, a vacuum pressure of 20 Pa, and a time of 20 hours to obtain an intermediate; calcining the intermediate at 500°C for 15 hours to obtain a composite carrier; Step 2: dissolve ammonium molybdate and nickel nitrate in deionized water, and adjust the pH to 7.5 with ethylenediamine to obtain solution A; dissolve ammonium metavanadate in deionized water, and stir to dissolve to obtain solution B; Step 3: Place the composite carrier in solution A, immerse it under vacuum for 1 hour, and then put it in an oven and dry it at 100°C for 10 minutes; Step 4: Place the composite carrier in solution B again, immerse under vacuum for 1 hour, place the impregnated composite carrier in a reaction kettle, and seal it; place the reaction kettle in an oven, hydroheat at 160° C. for 20 hours, and cool; Step 5: After the reactor cools to room temperature, the composite carrier is taken out, and after multiple ultrasonic washings, it is placed in an oven and dried at 80° C. for 20 h to obtain a catalyst precursor; Step 6, calcining the catalyst precursor at 500° C.; Step 7: Reduce the calcined product, the reducing gas (hydrogen) flow rate is 17 mL / min, the reduction time is 3 h; the reduction temperature is 580° C., and the heating rate is 6° C. / min, to obtain a hydrogenation catalyst.

[0036] Comparative Example A-1 The difference between Comparative Example A-1 and Example A-3 is that in step 2, ammonium metavanadate is not added.

[0037] Comparative Example A-2 The difference between Comparative Example A-2 and Example A-3 is that in step 2, ammonium molybdate and ammonium metavanadate are not added.

[0038] Comparative Example A-3 The difference between Comparative Example A-3 and Example A-3 is that in step 2, nickel nitrate and ammonium metavanadate are not added.

[0039] Comparative Example A-4 The difference between Comparative Example A-4 and Example A-3 is that in step 1, silica sol is not included.

[0040] Comparative Example A-5 The difference between Comparative Example A-5 and Example A-3 is that in step 1, alumina sol is not included.

[0041] Comparative Example A-6 The difference between Comparative Example A-6 and Example A-3 is that: (1) Step 1 is not included; (2) In Steps 3 and 4, conventional alumina carrier is used for impregnation. The conventional alumina carrier is an industrial product, clover-shaped, and has a length of (2~3) mm.

[0042] The physicochemical properties of the hydrogenation catalysts prepared in Examples A-1 to A-3 and Comparative Examples A-1 to A-6 were tested, and the results are shown in Table 1.

[0043] Table 1 Physical and chemical properties of hydrogenation catalysts prepared in Examples A-1 to A-3 and Comparative Examples A-1 to A-6 As shown in Table 1, the specific surface areas of Examples A-1 to A-3 are 200 to 400 m 2 / g, the proportion of macropore volume is 30~50%, and the proportion of mesopore volume is 50~65%. When a single alumina carrier (Comparative Example A-4) or a conventional alumina carrier (Comparative Example A-6) is used, the proportion of mesopores is significantly increased, and when a single silica carrier (Comparative Example A-5) is used, the proportion of macropores is significantly increased. When the type of active component loading is reduced (such as Comparative Example A-1 to Comparative Example A-3), the proportion of macropores is more and the proportion of mesopores is less. It has been found in practice that only within the pore volume range specified by the present invention can the hydrogenation catalyst play the maximum effect when used.

[0044] The preparation method of needle coke is described in detail below in conjunction with specific examples. It should be noted that the hydrogenation catalysts mentioned in the following examples and comparative examples are all sulfurized catalysts after sulfurization. The sulfurization conditions are: pressure 4.0 MPa, temperature 320°C, space velocity 1.25 h -1 , hydrogen-to-oil ratio is 450 / 1, and the sulfurized oil uses aviation kerosene containing 2% mass fraction of CS2.

[0045] The sulfurization steps of the hydrogenation catalyst are: (1) Load the hydrogenation catalyst into the reactor. After loading the catalyst, connect the nodes before and after the reaction tube, open the front hydrogen valve, check the air tightness of the device, and observe whether the pressure gauge of the device changes within 12 hours; (2) After confirming that the pressure gauge has no change and the device is not leaking, adjust the device pressure to a stable 4.0 MPa and adjust the hydrogen flow rate to stabilize it at 56.25 L / h; (3) Raise the temperature of the reaction tube to 150°C at a rate of 40°C / h and maintain the constant temperature for 2h (catalyst dehydration); (4) Start feeding the prepared sulfide oil at a feed rate of 125 mL / h. After the sulfide oil penetrates the reactor, continue to heat it (the process takes about 1 hour). (5) Heating at a rate of 40°C / h to 230°C and maintaining the temperature constant for 4h; (6) Heating at a rate of 40°C / h to 290°C and maintaining the temperature constant for 4h; (7) The temperature is raised to 320°C at a heating rate of 40°C / h, and vulcanization is completed.

[0046] Example B-1 A method for producing needle coke using FCC slurry oil mainly comprises the following steps: S1, filtering and separating step: using FCC oil slurry as raw material, filtering and separating to obtain FCC filtered oil; S2, vacuum distillation step: cutting the FCC filtered oil by vacuum distillation to obtain an aromatic narrow fraction oil at a distillation temperature of 390 to 440° C.; S3, solvent extraction step: subjecting the aromatic narrow fraction oil to solvent extraction treatment to enrich aromatic hydrocarbons to obtain extracted oil; S4, hydrogenation step: using the extracted oil as a raw material, hydrogenation is performed on the hydrogenation catalyst prepared in Example A-1 to remove the coke-prone components to obtain hydrogenated oil; the reaction temperature of the hydrogenation is 360° C., the reaction pressure is 10 MPa, and the reaction time is 150 min; S5, carbonization and coking step: the hydrogenated oil is carbonized and coked in stages, as follows: The first stage: the reaction pressure is 2 MPa, the temperature is increased to 380 °C at a heating rate of 12 °C / min and kept at this temperature for 2 h; The second stage: the reaction pressure is 2.5 MPa, the temperature is increased to 440 °C at a heating rate of 8 °C / min and kept at this temperature for 10 h; The third stage: the temperature is maintained at 440°C, the reaction pressure is increased to 20MPa, and the pressurization time is 0.5h; Stage 4: The reaction pressure is 1 MPa, the temperature is increased to 500 °C at a heating rate of 3 °C / min and kept at this temperature for 5 h; The fifth stage: cooling to room temperature to obtain green coke; S6, calcination step: crush and screen the green coke, take the sieve material and place it in a high-temperature furnace, introduce nitrogen, and stabilize the gas rate to 70 mL / min. After maintaining for about 20 minutes, under the protection of nitrogen, increase the temperature from room temperature to 800°C at a heating rate of 7°C / min, keep it warm for 2 hours, then increase the temperature to 1400°C at a heating rate of 2°C / min, and keep it at 1400°C for 120 minutes, then stop heating, cool it while continuously introducing nitrogen, until it drops below 400°C, stop introducing nitrogen, and naturally cool it to room temperature to obtain needle coke.

[0047] The microstructure of the needle coke prepared in this example was tested. The results are as follows: Figure 1 As shown by Figure 1 It can be seen that needle coke with a "needle-like" structure is indeed prepared by the preparation method of the present invention.

[0048] Example B-2 The difference between Example B-2 and Example B-1 is that: (1) in step S4, the extracted oil is used as the raw material, and the hydrogenation catalyst prepared in Example A-2 is used for hydrogenation treatment to remove the coke-prone components to obtain hydrogenated oil; the reaction temperature of the hydrogenation treatment is 400° C., the reaction pressure is 4 MPa, and the reaction time is 60 min; (2) in step S5, the hydrogenated oil is subjected to a staged carbonization and coking treatment, which is as follows: The first stage: the reaction pressure is 1 MPa, the temperature is increased to 380 °C at a heating rate of 10 °C / min and kept at this temperature for 1 h; The second stage: the reaction pressure is 2 MPa, the temperature is increased to 440 °C at a heating rate of 6 °C / min and kept at this temperature for 2 h; The third stage: the temperature is maintained at 440°C, the reaction pressure is increased to 18MPa, and the pressurization time is 0.5h; The fourth stage: the reaction pressure is 0.5 MPa, the temperature is increased to 500 °C at a heating rate of 2 °C / min and kept at this temperature for 1 h; The fifth stage: cooling to room temperature to obtain green coke.

[0049] Example B-3 The difference between Example B-3 and Example B-1 is that: (1) in step S4, the extracted oil is used as the raw material, and the hydrogenation catalyst prepared in Example A-3 is used for hydrogenation treatment to remove the coke-prone components to obtain hydrogenated oil; the reaction temperature of the hydrogenation treatment is 380° C., the reaction pressure is 8 MPa, and the reaction time is 100 min; (2) in step S5, the hydrogenated oil is subjected to a staged carbonization and coking treatment, which is as follows: The first stage: the reaction pressure is 1.5 MPa, the temperature is increased to 380 °C at a heating rate of 11 °C / min and kept at this temperature for 1.5 h; The second stage: the reaction pressure is 2.3 MPa, the temperature is increased to 440 °C at a heating rate of 7 °C / min and kept at this temperature for 8 h; The third stage: the temperature is maintained at 440°C, the reaction pressure is increased to 15MPa, and the pressurization time is 0.5h; Stage 4: The reaction pressure was 0.8 MPa, the temperature was raised to 500 °C at a heating rate of 2.5 °C / min and kept at this temperature for 4 h; The fifth stage: cooling to room temperature to obtain green coke.

[0050] Comparative Example B-1 The difference between Comparative Example B-1 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-1 is used.

[0051] Comparative Example B-2 The difference between Comparative Example B-2 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-2 is used.

[0052] Comparative Example B-3 The difference between Comparative Example B-3 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-3 is used.

[0053] Comparative Example B-4 The difference between Comparative Example B-4 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-4 is used.

[0054] Comparative Example B-5 The difference between Comparative Example B-5 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-5 is used.

[0055] Comparative Example B-6 The difference between Comparative Example B-6 and Example B-1 is that in step S4, the hydrogenation catalyst prepared in Comparative Example A-6 is used.

[0056] Comparative Example B-7 The difference between Comparative Example B-5 and Example B-1 is that step S5 does not include the third stage.

[0057] Comparative Example B-8 The difference between Comparative Example B-8 and Example B-1 is that in step S6, the raw coke is crushed and screened, the screened material is placed in a high-temperature furnace, nitrogen is introduced, and the gas rate is stabilized to 70 mL / min. After maintaining for about 20 minutes, under the protection of nitrogen, the temperature is increased from room temperature to 1400°C at a heating rate of 7°C / min, and the temperature is maintained at 1400°C for 120 minutes. After that, the heating is stopped, and the temperature is cooled while continuously introducing nitrogen until it drops below 400°C, then the introduction of nitrogen is stopped, and the temperature is naturally cooled to room temperature to obtain needle coke.

[0058] Comparative Example B-9 The difference between Comparative Example B-9 and Example B-1 is that: (1) in step S4, the hydrogenation catalyst prepared in Comparative Example A-1 is used; (2) in step S5, the third stage is not included. (3) in step S6, the raw coke is crushed and screened, the sieve material is placed in a high-temperature furnace, nitrogen is introduced, and the gas rate is stabilized to 70 mL / min. After maintaining for about 20 minutes, the temperature is increased from room temperature to 1400°C at a rate of 7°C / min under the protection of nitrogen, and the temperature is kept constant at 1400°C for 120 minutes before stopping heating, cooling while continuously introducing nitrogen until the temperature drops below 400°C, then the introduction of nitrogen is stopped, and the temperature is naturally cooled to room temperature to obtain needle coke.

[0059] The true density and thermal expansion coefficient of the needle coke prepared in all embodiments and all comparative examples were tested. The true density was measured using the GB / T2540-81 (88) method; the thermal expansion coefficient (CTE) was measured using the national standard GB3074-5-82 method. The results are shown in Table 2. It should be noted that the total aromatic hydrocarbon content in the extracted oil in step S3 of the present invention is 58.36%, the sulfur content is 0.73%, and the nitrogen content is 0.29%.

[0060] Table 2 Hydroprocessing and needle coke performance test results It can be seen from Table 2 that, compared with the comparative example, in Example B-1 to Example B-3, the hydrogenation catalyst of the present invention carried out deep hydrogenation treatment on the extracted oil, and the effect of this treatment process was remarkable, which was specifically reflected in the significant reduction of the sulfur content in the hydrogenated oil obtained after hydrogenation. Specifically, the sulfur content in the hydrogenated oil was successfully controlled at an extremely low level of not more than 0.35%. Compared with the untreated extracted oil, the sulfur content was reduced by at least 0.38%. This reduction is of great significance for improving the environmental performance of oil products and subsequent processing and utilization. At the same time, the hydrogenation treatment also brought about a significant decrease in nitrogen content. The nitrogen content in the hydrogenated oil was effectively reduced to a level below 0.10%. Compared with the extracted oil, the reduction in nitrogen content reached about 0.2%. In addition, the needle coke prepared by the method of the present invention has a true density of not less than 2.26 g / cm3 , the thermal expansion coefficient is not greater than 1.10×10 -6 / ℃, in summary, the needle coke prepared by the method of the present invention has excellent performance.

[0061] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for producing needle coke using FCC slurry oil, mainly comprising the steps of filtration separation, vacuum distillation, solvent extraction, hydrogenation treatment, carbonization to coke and calcination; characterized in that: In the hydroprocessing, the hydroprocessing is carried out in combination with the hydroprocessing catalyst after the sulfidation treatment; the hydroprocessing catalyst comprises a composite carrier and an active element, the mass percentage of the active element in the hydroprocessing catalyst is 10-45%, the active element comprises a main active element and a secondary active element, the main active element comprises Ni and Mo in a molar ratio of 1:(3-6), and the secondary active element is at least one of Co, V or W; The composite carrier contains 50-80% alumina and 20-50% silica by mass; the specific surface area of ​​the composite carrier is 200-400m 2 / g, a multi-level pore structure with micropores, mesopores and macropores, the size of the micropores is less than 2nm, the size of the mesopores is 2nm-50nm, and the size of the macropores is greater than 50nm; the ratio of the pore volume of the micropores to the total pore volume is <5%, the ratio of the pore volume of the mesopores to the total pore volume is 50-65%, and the ratio of the pore volume of the macropores to the total pore volume is 30-50%.

2. The method for producing needle coke using FCC slurry oil according to claim 1, characterized in that: The preparation method of the hydrogenation catalyst is: Step 1: polyvinyl alcohol, alumina sol, silica sol and urea solution are mixed to form a carrier precursor, and then liquid nitrogen is poured for rapid cooling, followed by freeze drying to obtain an intermediate; the intermediate is calcined at 400-600° C. for 10-20 hours to obtain a composite carrier comprising alumina and silica; Step 2: dissolve ammonium molybdate and nickel nitrate in deionized water, and adjust the pH to 7.1-8.0 with ethylenediamine to obtain solution A; Dissolve the metal salt containing the secondary active element in deionized water, and stir to dissolve to obtain solution B; Step 3: Place the composite carrier in solution A, immerse it in vacuum for 0.5 to 2 hours, and then place it in an oven and dry it at 100° C. for 10 minutes; Step 4: Place the composite carrier in solution B again, and immerse it under vacuum for 0.5 to 2 hours. Place the impregnated composite carrier in a reaction kettle and seal it. Place the reaction kettle in an oven, hydroheat it at 150 to 170° C. for 12 to 48 hours, and cool it. Step 5: After the reactor cools to room temperature, the composite carrier is taken out, and after multiple ultrasonic washings, it is placed in an oven and dried at 60-100°C for 12-24 hours to obtain a catalyst precursor; Step 6: calcining the catalyst precursor at 400-600° C.; Step 7: reducing the calcined product to obtain a hydrogenation catalyst.

3. The method for producing needle coke using FCC slurry oil according to claim 2, characterized in that: In step 1, the mass percentages of urea in polyvinyl alcohol, alumina sol, silica sol and urea solution are (1-2):(5-8):(2-5):(0.35-1).

4. The method for producing needle coke using FCC slurry oil according to claim 2, characterized in that: In step 1, the freeze-drying temperature is ≤-40°C, the vacuum pressure is ≤15Pa, and the time is 20~40h.

5. The method for producing needle coke using FCC slurry oil according to claim 2, characterized in that: In step 2, the metal salt containing the secondary active element includes at least one of cobalt nitrate, ammonium metavanadate or ammonium metatungstate.

6. The method for producing needle coke using FCC slurry oil according to claim 2, characterized in that: In step seven, the reduction conditions are: the reduction gas flow rate is 15-20 mL / min, the reduction time is 2-4 h; the reduction temperature is 550-600° C., and the heating rate is 2-8° C. / min.

7. The method for producing needle coke using FCC slurry oil according to claim 1, characterized in that: The FCC oil slurry is used as raw material, and FCC filtered oil is obtained through filtering and separation treatment; the FCC filtered oil is cut by vacuum distillation to obtain aromatic narrow fraction oil at a distillation temperature of 390-440°C; the aromatic narrow fraction oil is subjected to solvent extraction treatment to enrich aromatics to obtain extracted oil; the extracted oil is used as raw material, and hydrogenation treatment is carried out in combination with a sulfurized hydrogenation catalyst to remove coke-prone components to obtain hydrogenated oil; the hydrogenated oil is subjected to staged carbonization and coking treatment to obtain green coke; and finally the green coke is calcined to obtain needle coke.

8. The method for producing needle coke using FCC slurry oil according to claim 7, characterized in that: The hydrogenated oil is carbonized and coked in stages, as follows: The first stage: the reaction pressure is 1~2MPa, the temperature is increased to 380℃ at a heating rate of 10~12℃ / min and kept at this temperature for 1~2h; The second stage: the reaction pressure is 2~2.5MPa, the temperature is increased to 440℃ at a heating rate of 6~8℃ / min and kept at this temperature for 2~10h; The third stage: the temperature is maintained at 440℃, the reaction pressure is increased to 15~20MPa, and the pressurization time is 0.5h; The fourth stage: the reaction pressure is 0.5~1MPa, the temperature is increased to 500℃ at a heating rate of 2~3℃ / min and kept at this temperature for 1~5h; The fifth stage: cooling to room temperature to obtain green coke.

9. The method for producing needle coke using FCC slurry oil according to claim 8, characterized in that: The raw coke is crushed and screened, and the screened material is placed in a high-temperature furnace, and nitrogen is introduced at a stable gas rate of 70 mL / min. After maintaining for 20 minutes, under the protection of nitrogen, the temperature is increased from room temperature to 800°C at a heating rate of 7°C / min and kept warm for 2 hours, then increased to 1400°C at a heating rate of 2°C / min, and kept at 1400°C for 120 minutes. After that, the heating is stopped, and the temperature is cooled while continuously introducing nitrogen until it drops below 400°C, and the introduction of nitrogen is stopped. The temperature is naturally cooled to room temperature to obtain needle coke.

10. The method for producing needle coke using FCC slurry oil according to claim 7, characterized in that: The reaction temperature of the hydrogenation treatment is 360-400° C., the reaction pressure is 4-10 MPa, and the reaction time is 60-150 min.

Citation Information

Patent Citations

  • Production method of needle coke raw material

    CN101724420A

  • Preparation method of petroleum coke

    CN103666556A

  • Hydrorefining catalyst and preparation method thereof

    CN109692693A

  • Catalyst as well as preparation method and application thereof

    CN113304744A

  • Method for preparing needle coke with low thermal expansion coefficient by combination of fluidized coking and delayed coking

    CN113862033A

Cited By

  • Modified needle coke based on ethylene tar as well as preparation method and application of modified needle coke

    CN122381836A

  • Modified needle coke based on ethylene tar, its preparation method and application

    CN122381836B